Bridging the gap: Compressing non-unions for proper cellular signaling. (March 2022) - Kloen, P.; Loots, G.G.; Hamdy, R.C.; Smit, T.H.
Abstract: Non-unions of fractured bones are long-lasting painful conditions with a large socio-economic burden. Surgical intervention is the only treatment option, with firm compression of the bone fragments often resulting in non-union healing. Why compression works as a treatment for non-unions, however, remains poorly understood, because static loading is generally considered as non-osteogenic. In recent years, the crucial role of osteocytes and specific molecular pathways like the RankL/OPG, BMP and Sclerostin/Dkk1/Wnt axes have been identified as critical for bone healing. Furthermore, the role of mechanical loading and osteocyte deformation leading to a decrease or complete blocking of Sclerostin secretion – which in turn leads to activation of the osteogenic Wnt signaling pathway, has been elucidated. Our hypothesis states that osteocytes are the primary mediators of non-union healing. Therefore, in order to switch the resting osteocytes towards an osteogenic mode, firm compression of bone fragments is required for successful treatment of non-unions. This compression is necessary in order to restore the mechanical continuity of the bone, so that activities of daily life can physically stimulate the osteocytes, which in turn direct the bone healing process.